Optimization of decompression angles in facial nerve decompression surgery: A decompression model - Moeka Kanazawa; Fumihiro Mochizuki; Manabu Komori (PLoS ONE, 2026)
Facial nerve decompression is a surgical procedure performed for severe facial nerve paralysis associated with conditions such as Bell’s palsy and Ramsay Hunt syndrome. Classical Western studies by Fisch first established the surgical principles of facial nerve decompression, providing the foundation for subsequent work on decompression extent and outcomes. However, the optimal extent of bony decompression of the facial nerve canal remains unclear, and a 180° removal of the surrounding bone has traditionally been performed based on empirical judgment. Nevertheless, more extensive bone removal may increase the risk of surgical complications. This study aimed to evaluate the relationship between the angle of bony decompression around the facial nerve canal and pressure reduction, in order to determine the optimal decompression angle. To achieve this, a simplified experimental model was employed to quantitatively evaluate the relationship between decompression angle and internal pressure reduction, providing mechanical insight into facial nerve decompression rather than clinical data. To evaluate this relationship, a decompression model was created, and pressure changes were measured at opening angles ranging from 30° to 180°. The results revealed that a 150° decompression provided a comparable reduction in pressure to that of a 180° decompression. These findings suggest that the extent of bone removal can be minimized while still achieving sufficient pressure reduction, potentially lowering the risk of nerve injury. We also observed significant pressure reduction at 30°, suggesting utility in regions where extensive bone removal is difficult. The finding that a 150° decompression produced an effect comparable to that of 180° is an important contribution toward improving surgical safety. Moving forward, we aim to refine the decompression model and conduct further investigations using more detailed angle settings, with the goal of establishing a practical surgical technique.